Three new acylphloroglucinol glucosides from the roots of Lysidice rhodostegia and their antioxidant activities. (June 2020) - Wu, Chun; Li, Yingying; Yi, Xue; Xu, Yaping; Zhang, Yubo; Wang, Guocai; Li, Yaolan
Abstract: Three new acylphloroglucinol glucosides, rhodosides A-C (1 –3 ), and three known ones (4 –6 ) were isolated from the roots of Lysidice rhodostegia . The new structures were identified by MS, NMR, and acid hydrolysis. In addition, the antioxidant capacities of the isolated compounds were evaluated using DPPH radical-scavenging assay, and compounds 1 –6 exhibited obvious antioxidant activities with IC50 values of 24.65 ± 1.27 to 38.11 ± 1.35 μM. Graphical abstract: Image 1 Highlights: Three unknown acylphloroglucinol glucosides, rhodosides A-C, and three known ones were isolated from Lysidice rhodostegia . The new structures were elucidated by MS, NMR, and acid hydrolysis. All isolates were evaluated for antioxidant activities.